1981
DOI: 10.1002/bem.2250020309
|View full text |Cite
|
Sign up to set email alerts
|

Biological effects of long‐term exposure of rats to 970‐MHz radiofrequency radiation

Abstract: Rats (N = 16) exposed individually in circularly polarized waveguides to 970-MHz electromagnetic radiation (SAR = 2.5 mW/g, 22 h daily for 70 consecutive days) had significantly higher serum levels of triglycerides, albumin, and total protein compared with sham-irradiated controls. No difference was observed in the weights, hematologic profile, or in vitro lymphocyte responses to mitogens between these two groups. The higher serum levels of triglycerides in radiofrequency-radiation-exposed rats suggest a non-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 6 publications
1
6
1
Order By: Relevance
“…Beischer et al [1973] reported that serum triglycerides of blood samples decreased 14 h after supper when human subjects were exposed to a low-intensity magnetic field. However, higher serum levels of triglycerides were observed [Smialowicz et al, 1981] after rats were exposed to 970-MHz electromagnetic radiation.…”
Section: Discussionmentioning
confidence: 94%
“…Beischer et al [1973] reported that serum triglycerides of blood samples decreased 14 h after supper when human subjects were exposed to a low-intensity magnetic field. However, higher serum levels of triglycerides were observed [Smialowicz et al, 1981] after rats were exposed to 970-MHz electromagnetic radiation.…”
Section: Discussionmentioning
confidence: 94%
“…Nevertheless, the two studies also did not find statistically significant change for HDL-c level, which is inconsistent with our results. In addition, many animal studies also reported that exposure to EMF did not change the blood levels of TC (Celikozlu et al 2012;Kim et al 2006;Portet and Cabanes 1988;Smialowicz et al 1981;Torres-Duran et al 2007) or TG (Bahaoddini et al 2008;Elferchichi et al 2010;Hori et al 2012;Portet and Cabanes 1988;Torres-Duran et al 2007), while other studies found an increase in blood TC or TG (Smialowicz et al 1981), even a decrease in TC (Bahaoddini et al 2008;Bellossi et al 1998;Coskun and Comlekci 2010;Hori et al 2012;Luo et al 2007), TG (Bellossi et al 1998;Coskun and Comlekci 2010;Luo et al 2007) and HDL-c (Luo et al 2007). Methodological variations such as the difference of exposure conditions (e.g., resource type, frequency, intensity, duration, and continuity of EMF exposure), subjects' susceptibility, or detection methods may have given rise to such inconsistent findings across studies.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that multiple exposures at levels below the threshold were cumulative if done within 1 h of one another, but not if spaced 24 h apart, even if the sum of the energy absorption values exceeded the threshold. Smialowicz et al [1981] exposed 16 rats almost continuously for 69-70 consecutive days to 970 MHz RFEMF at 2.5 W/kg. There were no significant differences between RFEMF exposed and sham exposed rats in erythrocyte count, total or differential leukocyte counts, mean cell volume of erythrocytes, hemoglobin concentration, or hematocrit.…”
Section: Effects On Immunological Functionmentioning
confidence: 99%